Perancangan dan Implementasi Virtual Tour Sebagai Media Promosi Inovatif Pada Fakultas Ilmu Komputer - Nur Ichsan, Muhammad Adhe; Malabay (Fakultas Teknik Universitas Persada Indonesia YAI, 2024)
Esa Unggul University has experienced a decline in the number of applicants for the Faculty ofComputer Science, particularly in the Information Technology and Information Systems programs.To address this issue, a Virtual Tour application based on Virtual Reality (VR) was developedusing Unity and Oculus Quest 2 as a promotional tool. This application provides a deeper insightinto the campus facilities, enhancing prospective students' interest. The development method usedis the Multimedia Development Life Cycle (MDLC), encompassing planning, design, development,testing, and implementation stages. Testing results indicate that this application is effective inattracting new student interest. The Virtual Tour application has proven to be an innovative andbeneficial promotional tool for Esa Unggul University.